EFEKTIVITAS PSIKOEDUKASI PERKEMBANGAN SOSIOEMOSIONAL ANAK USIA 4-6 TAHUN DALAM MENINGKATKAN KOMPETENSI GURU PAUD: STUDI KASUS DI SKB KOTA BANDUNG - Safira Safira; Hanaa Azkia; Salma Salsabila; Fathin Khairunissa; Adzanishari Mawaddah (Journal of Innovation Research and Knowledge, 2026)
Socio-emotional development is a fundamental aspect of early childhood growth that significantly influences children's emotional regulation, social skills, and adaptive behavior formation. Early childhood education (PAUD) teachers play a key role in facilitating this developmental process; however, their pedagogical capacity to understand and respond to children's socio-emotional needs still requires strengthening. This psychoeducational program aims to enhance the understanding and competence of PAUD Negeri SKB Bandung City teachers regarding the socio-emotional development of children aged 4–6 years, encompassing core concepts, developmental milestones, and management strategies. The program was conducted on January 22, 2024, involving seven participants consisting of teachers and educational staff. The implementation method included a pre-test, material delivery, ice-breaking activities, and a post-test. Evaluation results demonstrated an increase in participants' understanding following the psychoeducation, reflected in more comprehensive and conceptual post-test responses including comprehension of complex emotions such as shame, pride, and guilt; awareness of environmental factors influencing children's emotions; the ability to design dynamic play activities; and more appropriate emotion management strategies. These findings indicate that psychoeducation is effective as a capacity-building intervention for PAUD teachers in supporting early childhood socio-emotional development.